2020
DOI: 10.3390/biology9120482
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequences of Serratia Strains Revealed Common Genes in Both Serratomolides Gene Clusters

Abstract: Serratia strains are ubiquitous microorganisms with the ability to produce serratomolides, such as serrawettins. These extracellular lipopeptides are described as biocides against many bacteria and fungi and may have a nematicidal activity against phytopathogenic nematodes. Serrawettins W1 and W2 from different strains have different structures that might be correlated with distinct genomic organizations. This work used comparative genomics to determine the distribution and the organization of the serrawettins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…This work intends to better understand the role of serratomolides, produced by Serratia strains, in PWD and, especially, to assess if they are effective against PWN. Serrawettin genes have already been found in several Serratia strains [30,[32][33][34][35][38][39][40][41] and were present in seven of nineteen selected strains. The swrW gene was present in five Serratia strains and swrA gene was present in two Serratia strains.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This work intends to better understand the role of serratomolides, produced by Serratia strains, in PWD and, especially, to assess if they are effective against PWN. Serrawettin genes have already been found in several Serratia strains [30,[32][33][34][35][38][39][40][41] and were present in seven of nineteen selected strains. The swrW gene was present in five Serratia strains and swrA gene was present in two Serratia strains.…”
Section: Discussionmentioning
confidence: 90%
“…Nineteen bacterial strains were screened by PCR for the presence of swrW and swrA genes since these genes are the key genes to all serrawettin biosynthetic gene clusters; however, each Serratia strain showed only one type when present [35]. The PCR products corresponding to the expected gene-fragments sizes were sequenced and compared with known serrawettin genes.…”
Section: Amplification Purification and Sequencing Of Swrw And Swra G...mentioning
confidence: 99%
See 2 more Smart Citations
“…The production of the antimicrobial biosurfactant lipopeptide Serratomolide isomers has so far been found in the genus Serratia, however, only in two species S. marcescens and S. surfactantfaciens and not yet in S. plymuthica (Wassermann et al, 1961;Clements et al, 2019). Recent genome comparison via antiSMASH software revealed that S. plymuthica AS9 carries the Serratomolide swrW gene (Marques-Pereira et al, 2020). Our findings now demonstrate the ability of S. plymuthica AS9 to produce Serratomolide biosurfactants, although further profound structural characterization of individual isomers is needed to give an insight into the full lipopeptide profile.…”
Section: Inter-and Intraspecific Variations Of Released Metabolitesmentioning
confidence: 99%